2016
DOI: 10.1097/wtf.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial support among refugees of conflict in developing countries

Abstract: Key implications for practice Refugees of conflicts in developing countries suffer more from secondary stressors than from trauma  Refugees have intrinsic psychosocial support mechanisms to respond to these stressors.  Shared social Identity plays an important role in these mechanisms. AbstractThe aim of this paper is to examine the psychosocial needs and stressors among refugees of conflicts in developing countries, and their group-based social support mechanisms. A systematic literature search of peer rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…One social context where the social identity approach has been relevant and that appears to have some features in common with the situation of refugees, is that of collective responses to an emergency or disaster (Alfadhli & Drury, 2016). In an emergency or disaster, people may find themselves in the same situation as other people who are affected, with their usual support mechanisms gone.…”
Section: Refugees As a Groupmentioning
confidence: 99%
“…One social context where the social identity approach has been relevant and that appears to have some features in common with the situation of refugees, is that of collective responses to an emergency or disaster (Alfadhli & Drury, 2016). In an emergency or disaster, people may find themselves in the same situation as other people who are affected, with their usual support mechanisms gone.…”
Section: Refugees As a Groupmentioning
confidence: 99%
“…The challenges arising from protracted displacement were analysed in a recent review of the literature, which found a wide range of secondary stressors among the refugees (Alfadhli & Drury, ). These secondary stressors (Lock et al, ) do not directly arise from the emergency (war) but are socially mediated (i.e., a function of social organization subsequent to the war).…”
Section: Introductionmentioning
confidence: 99%
“…The notion of shared identities as a resource for support among refugees is evident in some of the refugee literature (Alfadhli & Drury, ), though these accounts lack any psychological specification of the mechanisms involved and only include an occasional and general reference to the possible origin of this shared identity in common circumstances (e.g., Moulin, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to prolonged material deprivation, uncertainty and social exclusion which increase the risk of poorer mental health and emotional wellbeing. 47,48,49 Social integration and membership of social groups has been identified as key factors for good mental health in all citizens, and particularly important for refugees and asylum seekers. Ager & Strang (2004 50 ) developed a framework with 10 key indicators of integration: employment, housing, education, health, social bridges, social bonds, social links, language and cultural knowledge, safety and stability, and rights and citizenship.…”
Section: What Influences Mental Health and Emotional Wellbeing?mentioning
confidence: 99%
“…This may include increasing their knowledge about public transport, helping them to develop strategies to become more confident and less reliant on other family members for help, and encouraging them to attend specific events. 134,135 Given problems with discrimination and negative responses from the host community, it can be important to change their attitudes, so they are more welcoming and value what refugees and asylum seekers can contribute to their community. Host communities may feel threatened, for example, from perceptions that the new arrivals will compete with them for jobs, affordable housing and access to healthcare, or have different cultural identities and values.…”
Section: Social Support and Integrationmentioning
confidence: 99%